(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Valproic acid and meropenem is generally co-administrated in neurosurgical cases. Meropenem potentially decreases the valproic acid position, which may beget perioperative turn like seizure. Such serious adverse effect through potential interaction should be taken seriously and made aware by clinicians. Among various neurological emergencies status epilepticus is one of the most important and as it progresses, therapeutic control becomes difficult. Patients receiving antiepileptics and carbapenem group antibiotics concomitantly should be closely monitored due to possible drug interaction between these agents. The authors report a case of a 39-year-old male patient who was admitted with C4-C5 type C injury with neurological deficit due to road traffic accident. His Glasgow Coma Scale score was E4M2V1 and graded ‘A’ on Asia Impairment Scale. Patient was on treatment with valproic acid for existing schizophrenia. He was empirically treated with meropenem as cover antibiotic for infection due to phrenic nerve palsy that allowed secretions to be retained and increase the chance of infection. On third day of admission, he developed 2 episodes of breakthrough seizure in less than 5 minutes. Post status epileptic, Inj. Meropenem was stopped as cover antibiotic and he was treated with Inj. Fosphenytoin, Inj. Midazolam and Inj. Levetiracetam after which no such seizures were observed.